Pengembangan Augmented Reality Card Berbasis Morfologi Pisang untuk Pembelajaran Keanekaragaman Hayati di SMA - Bakari, Iswanto; Kandowangko, Novri Youla; Akbar, Muh Nur; Febriyanti, Febriyanti; Mustaqimah, Nur (Lembaga Sosial Rumah Indonesia, 2025)
Purpose – This study aims to describe the validity and practicality of augmented reality card media on biodiversity material for class X students of SMA Negeri 1 Telaga Biru, based on morphological studies of bananas (Musa spp).Method – This research used the research and development (R&D) method with the PLOM model. The media was developed using Assembler and Canva applications. Findings – The learning media developed in this research is in the form of augmented reality (AR) cards designed to improve students' understanding through interactive visualization of three-dimensional objects. This media combines print elements with digital technology, thus providing an interesting, contextual, and easy-to-understand learning experience. The results of the validity test showed that the media expert's assessment obtained an average score of 80% in the “Valid” category, while the material expert gave an average score of 85%, which was included in the “Very Valid” category. Overall, the average validity of the media reached 82% and was categorized as “very valid.” The practicality of the media was tested through teacher and learner response questionnaires, each of which obtained an average score of 95% and 89%, so that the total practicality reached 92% in the “Very Practical” category. Research Implications – Based on the results of the validity and practicality tests, the augmented reality card media is considered very valid and very practical, so it is feasible to use as a biology learning media, especially in high school biodiversity material.